Penurunan Ukuran Butir Serbuk Besi dengan Ball Milling 744 rpm dan Ball to Powder Weight Ratio 1:5 - Haris Cahyo Triatmono; Muslimin Muslimin; Lydia Anggraini (President University, 2017)
Creating a magnet with powder metallurgy technology, the materials to be processed must be available in powder form with a relatively very fine size, in micrometers (μm). In the magnetism of materials, grinding the material to obtain a very fine powder size is intended to obtain a magnetic material powder having a single domain. One tool commonly used to reduce the size of the powder to reach the size of a micrometer (μm) is a ball milling machine. This tool works by using hard balls in a drum. The balls are clashing each other with ground powder until the powder size becomes very small. Ball milling is using a strong material SS400, so it is expected to last long. While the special drum uses a base material of metal that is non-magnetic based Austenitic Manganese Steel. Ball uses a Ni-Hard ball. The AC motor measured with a stroboscope while carrying the load is 744 rpm. The process of smoothing that occurs inside the tube when the machine is run is the occurrence of collisions between Ni-Hard balls with the best grind sand is 83.3 grams with the number of Ni-Hard ball 101 fruit with a diameter of 10 mm and 75 pieces with a diameter of 11 mm, with using a 1:5 ratio. The process of shooting using Keyence optical microscope VHX 5000 with 200x bundle. Significant size changes occur with grinding with 10 mm diameter Ni-Hard ball from 15 minutes to 45 minutes. Then by using a Ni-Hard ball diameter of 11 mm also changed although not too significant.